The apheresis content analysis in Allo-HSCT represents reliable influential factors on graft-versus-host disease and overall survival. (April 2021) - Rauofi, Atefeh; Hajifathali, Abbas; Karami, Samira; Tavakoli, Farzaneh; Roshandel, Elham; Bonakchi, Hossein; Parkhideh, Sayeh
Highlights: The Apheresis cellular content is one of the possible factors influencing the (GVHD) and (OS) as transplantation outcome. A CD34 + cell and CD3 + cell dose was associated with higher survival and lower acute and chronic GVHD incidence. Graft cell dose lower than the cut-off level could lead to better outcomes after allogeneic transplantation. Abstract: Background: Hematopoietic stem cell transplantation (HSCT) is an established treatment for hematologic malignancies. However the post-HSCT outcome can be affected by multiple pre-transplant, transplant, and post-transplant factors. The cellular content of graft could be possible factors influencing the graft-versus-host disease (GVHD) and overall survival (OS) as transplantation outcomes. Purpose: The aim of this study was to assess the impact of infused CD34+ cells, CD3+ cells, and MNC count on the patients' survival and incidence of graft-versus-host disease (GVHD). Material and methods: We analyzed 87 patients with hematological malignancies who underwent allogeneic hematopoietic stem cell transplantation at the Taleghani Stem Cell Transplantation and Cell therapy center, Tehran, Iran from January 2016 to December 2018. Patients were conditioned with either myeloablative conditioning regimen or reduced-intensity regimen. Result: A CD34 + cell dose < 4.35 × 10 6 /kg and CD3 + cell dose < 365 × 10 6 /kg was associated with higher survival and lower acute and chronic GVHD incidence, although their association was not statistically significant. Moreover, there was a significant association between MNC count < 6.15 × 10 8 /kg and acute GVHD incidence. Conclusion: Graft cell dose, lower than the cut-off level, could lead to better outcomes after allogeneic transplantation. However, this study showed that future investigations are required in a larger population of patients in order to determine the exact effect of allogeneic graft cell dose on transplantation outcome.